Marigold and rose : a fiction - Glück, Louise, 1943- (Farrar, Straus and Giroux, 2022)
Marigold and Rose is an enchanting, playful, and absolutely singular fable from the Nobel laureate and Pulitzer Prize winner Louise Glück. Simultaneously sad and funny, and shot through with a sense of stoic wonder, this small miracle of a book, following thirteen books of poetry and two collections of essays, is unlike anything Glück has written, while at the same time it is inevitable, transcendent.